2021
DOI: 10.3390/ijms22063050
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Tubular pH by Acetazolamide in a Ca2+ Transport Deficient Mice Facilitates Calcium Nephrolithiasis

Abstract: Proximal tubular (PT) acidosis, which alkalinizes the urinary filtrate, together with Ca2+ supersaturation in PT can induce luminal calcium phosphate (CaP) crystal formation. While such CaP crystals are known to act as a nidus for CaP/calcium oxalate (CaOx) mixed stone formation, the regulation of PT luminal Ca2+ concentration ([Ca2+]) under elevated pH and/or high [Ca2+] conditions are unknown. Since we found that transient receptor potential canonical 3 (TRPC3) knockout (KO; -/-) mice could produce mild hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 68 publications
5
16
0
Order By: Relevance
“…By 2020, Khayyat et al 6 also noticed the here depicted disagreement on the TRPC3 expression in the nephron among different working groups, but did not contribute to the morphological understanding, rather focusing on functional aspects. Awuah Boadi et al 34 reported TRPC3 localization in distal tubular cells little later as supported by our immunostaining. Even though, almost no reports exist on TRPC3 and even less on TRPC5 in the distal tubule or its different segments, we reported the distribution in the different three segments for the sake of completeness.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…By 2020, Khayyat et al 6 also noticed the here depicted disagreement on the TRPC3 expression in the nephron among different working groups, but did not contribute to the morphological understanding, rather focusing on functional aspects. Awuah Boadi et al 34 reported TRPC3 localization in distal tubular cells little later as supported by our immunostaining. Even though, almost no reports exist on TRPC3 and even less on TRPC5 in the distal tubule or its different segments, we reported the distribution in the different three segments for the sake of completeness.…”
Section: Discussionsupporting
confidence: 85%
“…As mentioned above, especially this localization is poorly investigated with respect to TRPC3. In analogy to the function of TRPC3 in the proximal tubule 11 and to the function of TRPV5 in the distal tubule 11,46 , regulation of luminal [Ca 2+ ] could be suggested as a channel's function in this localization 11,34,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of those metabolic conditions, hypercalciuria, is considered to be the most common metabolic risk factor for calcium stone formation [9]. Meanwhile, renal tubular acidosis (RTA), which is characterized as defective renal acid-base imbalance due to the inability to secrete H + -atoms, may promote CaP formation in the RT [11].…”
Section: Introductionmentioning
confidence: 99%
“…The calcium‐sensing receptor (CaSR) is a G protein‐coupled receptor with seven transmembrane‐spanning domains, that modulate calcium homeostasis in the parathyroid glands and kidneys 10,11 . An increasing number of studies have reported that CaSR is closely linked with bone metabolism by sensing extracellular calcium (Ca 2+ e ) concentration and responding to its change.…”
Section: Introductionmentioning
confidence: 99%